An Etiological Study of Upper Gastrointestinal Bleeding - Sohail Bhutta , Muzamil Jamil , Kamran Aziz ,Wasim uddin (Journal of Rawalpindi Medical College, 2012)
Background: To determine the causes of upper gastrointestinal bleed in patients undergoing endoscopy Methods: In this prospective descriptive study 147 naive patients, with first episode of upper gastrointestinal bleeding, who underderwent endoscopic examination within 24 hours of their admission were included. Results:Mean age was 52.8 years. Majority ( 64.5%) were male. 30.6% patients had either a single or multiple duodenal or gastric ulcers. Thirty one (21%)patients had bleeding lower esophageal varices (LEV) or gastric varices. Another 3.4% patients had bleeding peptic ulcer in presence of non bleeding LEV . Duodenitis, gastric erosions and erosive gastritis were found in 18.4% . In 12.2% patients no cause of upper GI bleed was found. Conclusion: Peptic ulcer was found to be the commonest cause of upper GI bleed(34%). Gastro esophageal varices (21.1%) was the second commonest cause. Duodenitis, gastric erosions and erosive gastritis were among the less common causes(18.4%).